Protocol for the development of a core outcome set for respectful maternal and newborn care in a low-middle income setting. - Farai Marenga; Kushupika Dube; Unice Goshomi; Tina Lavender; Carol Bedwell; Jamie J Kirkham (PLoS ONE)
Introduction Disrespect and abuse have been seen as a real hindrance to achieving universal coverage for skilled delivery. Improving respectful maternal and newborn care and quality of care around the time of birth has been identified as a key strategy in low- and middle-income countries for reducing the rates of stillbirths and maternal and newborn mortality and morbidity rates. Currently, there is no core outcome set on respectful maternal and newborn care, resulting in reporting of various study outcomes from different studies which hinders the improvement of maternal and neonatal health. Objective To develop a core outcome set for respectful maternal and newborn care that can be used in research studies and clinical practice in low-middle income countries. Methods/design An exploratory sequential mixed methods evidence synthesis design will be adopted for the study. This design will enable the utilisation of the core outcome set development methodology in three stages. First, a systematic review and secondary analysis of qualitative interviews of women who utilise maternal care services will be undertaken in order to generate a list of outcomes. This will be followed by a two-round online Delphi study with multiple stakeholder groups which include women and their partners, women representative groups, parents, health workers and researchers. Each person will score the outcomes in terms of the defined criteria. Lastly, the results of the Delphi will be summarised and discussed at a virtual consensus meeting with representation from all stakeholder groups where the final core outcome set will be decided. Discussion The core outcome set will predominantly be developed for use in a low-middle income country setting to measure and improve the quality of respectful maternal and newborn services.